Clinically relevant fluoroquinolone resistance due to constitutive overexpression of the PatAB ABC transporter in Streptococcus pneumoniae is conferred by disruption of a transcriptional attenuator. (18th November 2014) - Baylay, Alison J.; Piddock, Laura J. V.
Abstract : Objectives: Constitutive overexpression of patAB has been observed in several unrelated fluoroquinolone-resistant laboratory mutants and clinical isolates; therefore, we sought to identify the cause of this overexpression. Methods: Constitutive patAB overexpression in two clinical isolates and a laboratory-selected mutant was investigated using a whole-genome transformation approach. To determine the effect of the detected terminator mutations, the WT and mutated patA leader sequences were cloned upstream of a GFP reporter. Finally, mutation of the opposing base in the stem–loop structure was carried out. Results: We identified three novel mutations causing up-regulation of patAB . All three of these were located in the upstream region of patA and affected the same Rho-independent transcriptional terminator structure. Each mutation was predicted to destabilize the terminator stem–loop to a different degree, and there was a strong correlation between predicted terminator stability and patAB expression level. Using a GFP reporter of patA transcription, these terminator mutations led to increased transcription of a downstream gene. For one mutant sequence, terminator stability could be restored by mutation of the opposing base in the stem–loop structure, demonstrating that transcriptional suppression of patAB is mediated by the terminator stem–loop structure. Conclusions: This study showed that a mutation in a Rho-independent transcriptional terminator structure confers overexpression of patAB and fluoroquinolone resistance. Understanding how levels of the PatAB efflux pump are regulated increases our knowledge of pneumococcal biology and how the pneumococcus can respond to various stresses, including antimicrobials.